Multi-color reflectance imaging of middle ear pathology in vivo - Valdez, Tulio A.; Spegazzini, Nicolas; Pandey, Rishikesh; Longo, Kaitlyn; Grindle, Christopher; Peterson, Donald; Barman, Ishan (Analytical and bioanalytical chemistry, 2015)
Otoscopic examination using white-light illumination has remained virtually unchanged for well over a century. However, the limited contrast of white-light otoscopy constrains the ability to make accurate assessment of middle ear pathology and is subject to significant observer variability. Here, we employ a modified otoscope with multi-color imaging capabilities for superior characterization of the middle ear constituents in vivo and for enhanced diagnosis of acute otitis media and cholesteatoma. In this pilot study, five patients undergoing surgery for tympanostomy tube placement and congenital cholesteatoma excision were imaged using the custom-designed multi-color video-rate reflectance imaging system. We show that the multi-color imaging approach offers an increase in image contrast, thereby enabling clear visualization of the middle ear constituents, especially of the tympanic membrane vascularity. Differential absorption at the multiple wavelengths provides a measure of biochemical and morphological information, and the rapid acquisition and analysis of these images aids in objective evaluation of the middle ear pathology. Our pilot study shows the potential of using label-free narrow-band reflectance imaging to differentiate middle ear pathological conditions from normal middle ear. This technique can aid in obtaining objective and reproducible diagnoses as well as provide assistance in guiding excisional procedures.